A survey on the level of user acceptance towards MyKad multi-application : a study in Shah Alam and Pasir Puteh residential area / Nor Azleen Azib - Azib, Nor Azleen (2005)
Smart card technology remains novel for all the parties involved and nowadays great efforts are done to deploy the technology on wide scale base. Day-by-day, the technology are improving to enhance people life style and thus smart card also existed with multiplication. Means, there are various function and capabilities in a single card. This study is focusing on the MyKad, which is Malaysian Identity Smart Card multiplication. With a population of 23 million, the country of Malaysia has recently proven itself to be a technological innovator, implementing a project that has improved government service to citizens and increased economic activity for the entire nation. The Government Multi-purpose Card (GMPC) project is part of Malaysia's Multimedia Super Corridor (MSC) initiative —designed to attract leading-edge technology development to Malaysia. However, the since the date MyKad was launched the level of usage by its holder is still little. People seem very happy with the features provided in the card but the environments do not show the usage of its multiplication. Seem, it is great effort done to provide Malaysian with convenience. However, it is waste of effort if Malaysian did not fully utilized MyKad function and capabilities. The main objective of conducted this research are to study and analyze the acceptance of MyKad usage as the first and foremost multiplication card among Malaysian and it is hoped that the findings will be use to recommend solutions and actions of MyKad issues that will arise during the to the party involved. The findings is emphasize on user perception and not about MyKad itself, means that some issue like security, technology and so forth. In the meantime, this study is actually give worth for Malaysian generally. The findings show that Malaysian are willing to use MyKad multi-application but there is no enough supported environment to use it. There should be increase the effort by government, private sector and user themselves to utilize MyKad function.